Classical Psychedelics as Therapeutics in Psychiatry – Current Clinical Evidence and Potential Therapeutic Mechanisms in Substance Use and Mood Disorders - Mertens, Lea J.; Preller, Katrin H. (Pharmacopsychiatry, 2021)
Classical psychedelics, primarily psilocybin and lysergic acid diethylamide (LSD), have been used and extensively studied in Western medicine as part of substance-assisted psychotherapy in the 1950s and 1960s. Modern clinical research is currently gaining momentum and provides new evidence for the safety and efficacy of classical psychedelics (primarily psilocybin, but also LSD and ayahuasca) in the treatment of different psychiatric conditions, including substance use and mood disorders.In this review article, we outline common pathological mechanisms of substance use disorders (SUD) and unipolar depression. Next, the current literature on the effects of psychedelics is summarized in order to generate hypotheses regarding their potential therapeutic mechanisms of action in treating these psychiatric conditions. Finally, we review and discuss clinical trials published since 2011 investigating the effects of psychedelics in SUD and depression.While results from those modern clinical trials are promising, most of them do not meet the methodological requirements to allow firm conclusions on the clinical efficacy of psychedelics. Larger, blinded, randomized controlled trials (RCT) with clearly defined patient groups and well-defined primary endpoints are needed. Additionally, the therapeutic mechanisms of classical psychedelics are currently unknown. This review presents hypotheses derived from preclinical and human studies that need to be tested in future trials to better understand the clinical potential of psychedelic substances in modern psychiatry.
Keywords: classical psychedelics; substance use disorder; depression; pathological mechanisms; clinical trials